Ethnobotanical study on medicinal plants used by the Rajapur Saraswat Community of Dakshina Kannada, the Western Ghats of India - Yogeesha, Anadka; Pradeep, Bhat; Krishnakumar, Gulimane (Ethnobotany Research and Applications, 2026)
Background: The indigenous Rajapur Saraswat community in Dakshina Kannada district uses variety of herbal remedies to manage their primary healthcare needs. A large number of modern synthetic drugs are also available to serve the purpose, but they are often associated with severe side-effects. There are no previous reports on the documentation of ethno-medicinal information of this community. Methods: An ethnobotanical survey of the Rajapur Saraswat community was conducted from 2023 to 2025 in the rural areas of Dakshina Kannada district, Karnataka state, India. A total of 29 traditional practitioners were interviewed through semi-structured, open-ended discussions using a questionnaire. The gathered data was analyzed using qualitative descriptive methods, and quantitative tools such as use value (UV), relative frequency of citation (RFC), and informant consensus factor (ICF). Results: In total, 99 plant species belonging to 41 families were reported to have medicinal value and were used by the local community across the studied sites. The Fabaceae family was the most dominant family in terms of species diversity (7 species), followed by Lamiaceae (6 species), Apocyanaceae, Malvaceae, Phyllanthaceae and Rutaceae (5 species each), Euphorbiaceae, Myrtaceae, Poaceae and Rubiaceae (4 species each), Acanthaceae, Apiaceae and Combretaceae (3 species each). The plant species that have exhibited the highest RFC values are Curcuma longa (0.62), followed by Tinospora cordifolia and Piper nigrum (0.52 each), Aristolochia indica and Leucas aspera (0.48 each), Cuminum cyminum, Ziziphus oenoplia and Hemidesmus indicus (0.45 each), Zingiber officinale, Coriandrum sativum, Jasminum grandiflorum, Ocimum tenuiflorum and Ventilago maderaspatana (0.41 each), Senegalia catechu and Plectranthus amboinicus (0.38 each). Respiratory ailments had maximum agreement between informants (ICF=0.86) followed by digestive system (ICF=0.83), oral, dental, ear and nose category (ICF=0.82), dermatological (ICF=0.77), metabolic (ICF=0.75), fever (ICF=0.74), poisonous bites (ICF=0.73), urinary system (ICF=0.72), neurological and musculoskeletal (ICF=0.71), gynecological (ICF=0.58) and circulatory system (0.54). The plant species, Cassia fistula was reported to have the highest UV (1.00), followed by Litsea wightiana and Breynia vitis-idaea (0.67 each), and Ficus racemosa (0.57). The highest number of mentions was for Curcuma longa (seven), followed by Cuminum cyminum (six), Aristolochia indica, Ixora coccinea, Piper nigrum, and Senegalia catechu (five each). Considering the conservation status, Syzygium travancoricum is listed as Critically Endangered, Syzygium caryophyllatum as Endangered, Aporosa cardiosperma as Vulnerable, and Aegle marmelos as Near Threatened, as per the IUCN Red List. Conclusions: The findings reveal a rich diversity of plant species used for various ailments, with notable emphasis on formulations such as decoctions and juices for oral administration. The high ICF values recorded in this study suggest strong agreement on medicinal formulations among practitioners in the Rajapur Saraswat community. However, further interdisciplinary studies are needed to validate the therapeutic potential of medicinal plants to discover new drugs. Keywords: Ethnobotany, Rajapur Saraswat, traditional knowledge, Dakshina Kannada